Pengaruh Metode Quantum Reading terhadap Keterampilan Membaca Pemahaman Siswa Kelas VIII SMP Islam Nurul Karomah Tahun Ajaran 2024/2025: The Influence of the Quantum Reading Method on the News Text Reading Comprehension Skills of 8thGrade Students at SMP Islam Nurul Karomahin the 2024/2025 - Sonia, Gina; Agustiani, Tanti; Suparman, Fauziah (Universitas Tidar, 2025)
Reading comprehension is an essential skill that students must master in learning activities, particularly in Indonesian language learning. Good reading comprehension skills enable students to grasp key information, understand text structure, and summarize presented material. This research aims to determine the effect of the Quantum Reading method on the reading comprehension skills of eighth-grade students at SMP Islam Nurul Karomah in the 2024/2025 academic year. The research employs a quantitative experimental method using a One-Group Pretest Posttest Design. This design involves two tests: pretest and posttest. The pretest assesses students' initial abilities, followed by treatment using the Quantum Reading method. Subsequently, a posttest is conducted to evaluate the learning outcomes after the treatment. The research findings indicate an improvement in students' reading comprehension skills after the application of the Quantum Reading method. The initial observation through the pretest shows an average student score of 63,86 categorized as sufficient. However, after the treatment and posttest, the average score significantly increased to 86,36 categorized as good. This result is supported by the t-test analysis, which shows a t-value of 27,27 greater than the t-table value of 1,720 at a 0,05significance level. Therefore, the null hypothesis (H₀) is rejected, and the alternative hypothesis (H1) is accepted. This proves that the Quantum Reading method significantly influences the improvement of reading comprehension skills in news texts among eighth-grade students at SMP Islam Nurul Karomah in the 2024/2025 academic year.